Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.2663
|View full text |Cite
|
Sign up to set email alerts
|

SAT0120 Evaluation of the risk of overall malignancy and malignant lymphoma with methotrexate and biological agents in patients with rheumatoid arthritis based on the iorra cohort during a 14-year observation period

Abstract: BackgroundWhile dramatic progress has been made in this decade with treatments for rheumatoid arthritis (RA), such as methotrexate (MTX) and biological agents, concern about the safety, including the occurrence of malignancy, of these highly effective drugs still exists in daily clinical practice. There has not been an evident association between the use of biological agents and the occurrence of malignancy in most reports from clinical trials1 and observational studies2, although MTX use might be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Integrating MM in to current RA care strategies may help achieve better patient outcomes. 3 Rheumatology, University Hospital, Lille; 4 Rheumatology, University Hospital, Clermont-Ferrand; 5 Rheumatology, University Hospital, Bordeaux; 6 Rheumatology, University Hospital, Strasbourg; 7 Pain center, University Hospital, Paris, France Background: Although pain in rheumatoid arthritis (RA) is frequently thought to be inflammatory in nature, some studies reported clinically significant pain despite relatively low rheumatoid arthritis (RA) disease activity. Less than 50% of patients are satisfied by the management of pain.…”
Section: Resultsmentioning
confidence: 99%
“…Integrating MM in to current RA care strategies may help achieve better patient outcomes. 3 Rheumatology, University Hospital, Lille; 4 Rheumatology, University Hospital, Clermont-Ferrand; 5 Rheumatology, University Hospital, Bordeaux; 6 Rheumatology, University Hospital, Strasbourg; 7 Pain center, University Hospital, Paris, France Background: Although pain in rheumatoid arthritis (RA) is frequently thought to be inflammatory in nature, some studies reported clinically significant pain despite relatively low rheumatoid arthritis (RA) disease activity. Less than 50% of patients are satisfied by the management of pain.…”
Section: Resultsmentioning
confidence: 99%